PENGELOLAAN PEMBELAJARAN BAHASA INDONESIA SISWA SD MELALUI TEKNIK REKA CERITA GAMBAR - Maryam Maryam Maryam (Manajer Pendididikan, 2016)
The purpose of the research was improve the sucessfull learning management in Bahasa Indonesia using picture. The technique collecting the data using test and observation, the throughof apply to picture story Reka could improve the student result of study. In the first cycle the student get score 69,24, the second cycle improved to 74,88 and the thrid cycke the student getresult 76,92. In the post-test so that wasn;t student get bad score. So the result of the research showed the application of the technique Picture Story Reka could improve the student ability inBahasa Indonesia learning in the composition writing aspectKeywords: improvement , management, picture